SHORT COMMUNICATIONThe lung function in operated acquired mitral and aortic valve diseases without left ventricular failure – preliminary observations before operation - Bitner, Mirosław; Nowak, Dariusz (Archives of Medical Science, 2005)
Introduction: The study has been designed to evaluate the influence of the operations on cardio-pulmonary by-pass, particulary with systemic normothermia and cold crystalloid cardioplegia on the function of heart and lungs. Material and methods: 27 non-smokers 21-78 year old, 16 with aortic, 11 mitral valve diseases, 22 in NYHA III, 5 – IV class, randomly chosen pursuing excluding criteria before operation. Bodypletysmography, spirometry, and diffusing capacity were compared to the control group, and with American Thoracic Society (ATS) norms. Results: Following patients\' data values were significantly worse: Vital Capacity (p<0.05) – sitting position, and in sitting and supine positions: Forced Vital Capacity (p<0.001), Alveollar Volume (VA, p<0.05), Hemoglobin standardized Lung Diffusing Capacity for Carbon monoxide (TLCOc; p<0.05), and body surface area standardized TLCOc (TLCOc/BSA; p<0.001), whereas TLCOc/VA – insignificantly. After changing the position from sitting to supine most changes are similar, but the patients lacked a fall in percent-normal Residual Volume (RV), unlike in RV % Total Lung Capacity. Conclusions: Mild restrictive lung dysfunction is associated with acquired valve diseases before left ventricular failure develops, and respiratory adaptation to the supine position is almost unaffected.